Coaching style, sport enjoyment, and intent to continue participation among artistic swimmers - Kim, S.; Park, S.; Love, A.; Pang, T. C. (International Journal of Sports Science & Coaching, 2021)
Using situational leadership models, the current study examined direct and indirect relationships between coaching styles (i.e., democratic and autocratic) and athletes` intent to continue participation via enjoyment in the sport of artistic swimming. Data were collected using an online survey with a snowball sampling method. A total of 202 artistic swimmers at the elite level from 22 countries participated in this study. The findings showed that participants who trained with democratic-style coaches reported higher levels of athletic enjoyment and intent to continue their athletic careers. There was no mediating effect of athletic enjoyment between coaching styles and intent to continue via athletic enjoyment; instead, the results revealed that the direct path between athletic enjoyment and intent to continue was not significant. However, the results supported the direct relationships between both coaching styles and athletic enjoyment and between autocratic coaching style and intent to continue an athletic career.